EFFECT OF DIFFERENT MEDIA AND pH ON GROWTH AND SPORULATION OF DIFFERENT NATIVE TRICHODERMA SPP - M. K. ROY; S. HEMBRAM; A. DEBNATH (The Bioscan, 2015)
Different native Trichoderma isolated from agricultural soils were tested in vitro for suitable media, their pH levels tolerance and sporulation. The colony growth diameter and sporulation of fungi were greatly influenced by the different type of growth medium and pH. Keeping this back ground in mind the present work was undertaken.Variation in mycelial growth and fungal sporulation was observed at different media tested. On the basis of microscopic observation and growth characteristics,two native T Pun and T Pun2 isolates were tenta- tively identified as Trichodermavirens and Trichodermaharzianum, respectively. Colony radial growth and sporu- lation of native Trichoderma isolates was found to be excellent on Potato Dextrose Agar followed by Oat meal agar medium at optimal environmental conditions. All the Trichoderma isolates can grow at pH range between 5 and 8.Isolates T Pun2 and T Pun showed growth at all the pH, but the combination of growth (75.77, 70.87) and sporulation (7.85×10 7, 6.0×10 7 ) was found to be best at pH 6 respectively. Whereas, least growth (57.53, 63.23) of T Pun2 and T Pun isolates were found at pH8 and minimum sporulation (1.8×10 7, 2.87×10 7 ) were also observed in TSM medium respectively.